Domestic Violence against Women and Their Mental Health: Exploring the Impact of Domestic Violence on Mental Health of Indian Women (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Domestic violence is an intentional and frequent abusive behaviour which is based on unequal position of power. Domestic violence is a behaviour used by one person to control another one in family. Domestic violence has many forms it may be physical, psychological, emotional, sexual, economical (manipulation, deprivation) and several times it may be the combination of several of these. Domestic violence is prevalent among Indian women. It is significantly associated with poor mental and physical health of a woman. Battered women experience extreme level of depression, low self esteem, anxiety etc. In this study interview schedule was prepared to assess the domestic violence. 80 women were interviewed of village Sinser, district Jind, state Haryana. The study showed alcoholism and unemployed state of husband are the main reason of the domestic violence. Birth of a girl child and dowry are also the reasons of domestic violence. Many battered women had knowledge about law, but due to family pressure they do not take step against the violence. They also think it as stigma that’s why they avoid telling others about the violence.